2019
DOI: 10.1590/1980-0037.2019v21e60248
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of maturation and physical performance in basketball athletes of different playing positions

Abstract: The aim of this study was to compare the characteristics of somatic maturation, anthropometric and physical performance (vertical jump and aerobic power) in young basketball players of different playing positions (under 13 years) and analyze these relationships using Peak Height Velocity (PHV) as a measure of somatic maturation. For this, 26 male athletes were evaluated. Anthropometric variables were: body mass, standing and sitting height, and length of lower limbs. Maturation was determined by age at PHV. Ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 25 publications
0
1
0
Order By: Relevance
“…Training staff should account for training age, level of physical maturity, and movement competency when selecting a periodization scheme. As previously mentioned, adolescent females will undergo a phase of physical and neuromuscular change that can influence performance (13,104). A scheme with substantial variations in intensity and volume accompanied with higher loads, which can be seen more in block and undulating training schedules, may not be appropriate for female adolescent athletes and may put them at greater risk of injury (72).…”
Section: Periodizationmentioning
confidence: 99%
“…Training staff should account for training age, level of physical maturity, and movement competency when selecting a periodization scheme. As previously mentioned, adolescent females will undergo a phase of physical and neuromuscular change that can influence performance (13,104). A scheme with substantial variations in intensity and volume accompanied with higher loads, which can be seen more in block and undulating training schedules, may not be appropriate for female adolescent athletes and may put them at greater risk of injury (72).…”
Section: Periodizationmentioning
confidence: 99%
“…In addition, the existing literature pertaining to internal training demands of youth basketball players does not address the apparent position-specific differences (34). Position-specific differences in basketball are distinct and important because they are dictated by the technical and tactical roles they play (36,39) and inform the off-court physical development process (3). For instance, Svilar et al (38) reported greater RPE and sRPE for Guards when compared with Forwards and Centers among professional players.…”
Section: Introductionmentioning
confidence: 99%
“…Sport is selective, chiefly during adolescence, and often occurs along a maturity-related gradient. Many studies have analyzed the influence of maturity status on physical, physiological, and performance characteristics in soccer, basketball, or handball players [13,14,[16][17][18][19], but less information exists on male volleyballers. Albaladejo-Saura and colleagues reported that volleyball players with a more advanced state of maturation exhibited higher values of height, arm span, sitting height, bone diameters, muscle perimeters and fat, muscle and bone masses, and better performance achieved in medicine ball throwing and in countermovement jump (CMJ) than their chronological age peers [20].…”
Section: Introductionmentioning
confidence: 99%